Functional architecture of low-frequency variants highlights strength of negative selection across coding and non-coding annotations. - Gazal, Steven; Loh, Po-Ru; Finucane, Hilary K; Ganna, Andrea; Schoech, Armin; Sunyaev, Shamil; Price, Alkes L (Nat Genet, 2018)
Common variant heritability has been widely reported to be concentrated in variants within cell-type-specific non-coding functional annotations, but little is known about low-frequency variant functional architectures. We partitioned the heritability of both low-frequency (0.5%≤ minor allele frequency <5%) and common (minor allele frequency ≥5%) variants in 40 UK Biobank traits across a broad set of functional annotations. We determined that non-synonymous coding variants explain 17 ± 1% of low-frequency variant heritability ([Formula: see text]) versus 2.1 ± 0.2% of common variant heritability ([Formula: see text]). Cell-type-specific non-coding annotations that were significantly enriched for [Formula: see text] of corresponding traits were similarly enriched for [Formula: see text] for most traits, but more enriched for brain-related annotations and traits. For example, H3K4me3 marks in brain dorsolateral prefrontal cortex explain 57 ± 12% of [Formula: see text] versus 12 ± 2% of [Formula: see text] for neuroticism. Forward simulations confirmed that low-frequency variant enrichment depends on the mean selection coefficient of causal variants in the annotation, and can be used to predict effect size variance of causal rare variants (minor allele frequency <0.5%).
Keywords: Alleles; Biological Specimen Banks; Gene Frequency; Genetic Variation; Genetics, Population; Genome-Wide Association Study; Humans; Linkage Disequilibrium; Molecular Sequence Annotation; Open Reading Frames; Polymorphism, Single Nucleotide; Selection, Genetic; United Kingdom; White People

Linkage disequilibrium-dependent architecture of human complex traits shows action of negative selection. - Gazal, Steven; Finucane, Hilary K; Furlotte, Nicholas A; Loh, Po-Ru; Palamara, Pier Francesco; Liu, Xuanyao; Schoech, Armin; Bulik-Sullivan, Brendan; Neale, Benjamin M; Gusev, Alexander; Price, Alkes L (Nat Genet, 2017)
Recent work has hinted at the linkage disequilibrium (LD)-dependent architecture of human complex traits, where SNPs with low levels of LD (LLD) have larger per-SNP heritability. Here we analyzed summary statistics from 56 complex traits (average N = 101,401) by extending stratified LD score regression to continuous annotations. We determined that SNPs with low LLD have significantly larger per-SNP heritability and that roughly half of this effect can be explained by functional annotations negatively correlated with LLD, such as DNase I hypersensitivity sites (DHSs). The remaining signal is largely driven by our finding that more recent common variants tend to have lower LLD and to explain more heritability (P = 2.38 × 10); the youngest 20% of common SNPs explain 3.9 times more heritability than the oldest 20%, consistent with the action of negative selection. We also inferred jointly significant effects of other LD-related annotations and confirmed via forward simulations that they jointly predict deleterious effects.
Keywords: Alleles; Chi-Square Distribution; Datasets as Topic; Genetic Fitness; Genetic Variation; Humans; Linkage Disequilibrium; Models, Genetic; Molecular Sequence Annotation; Multifactorial Inheritance; Polymorphism, Single Nucleotide; Selection, Genetic